2020
DOI: 10.4314/ijbcs.v13i6.20
|View full text |Cite
|
Sign up to set email alerts
|

Etude de la qualité rédactionnelle des bulletins d’analyses biologiques au CHU Yalgado Ouédraogo, Burkina Faso

Abstract: RESUMELa non-conformité des bulletins d'analyses biologiques (BAB) rend difficile la réalisation et l'interprétation des résultats des examens biologiques. Elle compromet de ce fait l'utilisation optimale et rationnelle de l'outil d'aide au diagnostic que constituent les laboratoires. L'objectif de cette étude était d'évaluer la conformité des bulletins d'analyses biologiques prescrits et leur impact économique au Centre Hospitalier Yalgado Ouédraogo (CHU-YO), Burkina Faso. Il s'est agi d'une étude transversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…The identity (name or unique identifier) was specified in 97.11%, the signature was notified in 93.48% of the cases and the stamp was present in 85.78% of the requests. These results are similar to those obtained by Yacouba et al who showed that the identity (name and surname) of the prescribers was mentioned in 94.10%, the signature was present in 94.20% and the stamp in 44.10% of cases [17].…”
Section: Prescriber Informationsupporting
confidence: 91%
See 2 more Smart Citations
“…The identity (name or unique identifier) was specified in 97.11%, the signature was notified in 93.48% of the cases and the stamp was present in 85.78% of the requests. These results are similar to those obtained by Yacouba et al who showed that the identity (name and surname) of the prescribers was mentioned in 94.10%, the signature was present in 94.20% and the stamp in 44.10% of cases [17].…”
Section: Prescriber Informationsupporting
confidence: 91%
“…The majority of information on the requests for examinations was first and last name (99.77%), sex (80%) and age (60.06%). These results are close to those of Yacouba et al who show that the majority of the information on the patients was first and last name (99.80%), age (96.70%) and sex (94.30%) [17]. In addition, only 23.79% of requests had the relevant clinical information reported, which is lower than the 33.30% obtained by Onyiaorah et al in 2012 [20].…”
Section: Patient Informationsupporting
confidence: 84%
See 1 more Smart Citation
“…A biological test report is a medical prescription for diagnostic purposes, specifying the parameter to be measured, in relation to the diagnostic hypothesis envisaged, and all the information needed for the laboratory to carry out the test correctly ( 1 ). Non-compliance in the prescription of medical biology tests makes it difficult to carry them out and interpret the results ( 2 ). A number of researchers have concluded that non-compliance has a number of possible consequences for patients, such as misdiagnosis, mismanagement and treatment, as well as therapeutic abstention ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have concluded that non-compliance has a number of possible consequences for patients, such as misdiagnosis, mismanagement and treatment, as well as therapeutic abstention ( 3 ). In Burkina Faso, 59.4% of non-compliances concerning clinical information were reported in a study in 2021 ( 2 ). In Niger, Djobo et al recorded 53.99% of non-compliances concerning failure to notify the name of the service on biological examination forms ( 4 ).…”
Section: Introductionmentioning
confidence: 99%